Reflections on inequality and equality. - Ringen, Stein (My University, 2006)
Der Autor reflektiert den Begriff der sozialen Ungleichheit vor dem Hintergrund des sich seit Mitte der 1970er Jahre in Europa sich weiter öffnenden Schere in der Einkommensverteilung und der weitgehenden Akzeptanz dieses Prozesses - in einem ersten Abschnitt mit Überlegungen zu Egalitarimus, Gleichheit, Ungleichheit hinsichtlich Chancen und Bedingungen. Die nächsten Abschnitte gehen auf die Ungleichheit zwischen Personen (unterschiedlichen Einkommens, auch etwa in Bezug auf Arbeitsleistung und Lebensalter) und zwischen Gruppen (Niedrige Klasse, Arme, Frauen, Alte, Kinder, Behinderte, Minoritäten) ein. Der Frage der Daten(erhebung), der Indices, der Messung von Ungleichheit gilt der letzte Abschnitt. goj/difu

Here are two observations: - Since about 1975, there has been a shift, sometimes massively, towards more inequality in the distribution of income (and wealth) in most European countries. This shift seems to have been absorbed in society with little or no counter-reaction or difficulty. - In late 2005 and early 2006 France exploded in social riots of almost revolutionary proportions. Those riots would seem to have something to do with inequality, but how and what kind of inequality? These are simple yet puzzling examples. It seems to me that if we are to claim some theoretical understanding of inequality, we would have to be able to make sense of elementary observations such as these which are apparently totally contradictory. I take these observations as my test and will try to see if there is a way of reconciling them. The purpose of this essay is exactly what the title says: to reflect. I have wanted to take a step back from current research and think again about core concepts. These reflections are grounded in my own recently published or completed work, both theoretical and empirical. But presently I have wanted to reflect freely, and as naively as I have been able to, on the meaning of equality, inequality and the politics of egalitarianism. difu
Keywords: Gesellschaftsordnung; Armut; Einkommensverteilung; Sozialindikator; Soziale Ungleichheit; Gleichheit; Lebensstandard; Soziale Lage; Soziale Gruppe; Benachteiligung